Size and Duration of Multinodular Goiter Predicts Its Toxicity - Khalid, Abdul; Bukhari, Murtaza; Ahmed, Kh. Imtiaz; Ahmed, Ashfaq (International Journal of Pathology, 2018)
Objective: To evaluate the status of thyroid function in large multinodular goiters of more than 20 years duration.Study design: Prospective, observational studyPlace and duration of study: Department of Medicine Abbas Institute of Medical Sciences (AIMS) Muzaffarabad.The study included data from Jan 2011 to Dec 2012.Materials and Methods: Patients with large multinodular goiters (MNG) of more than 20 years duration wereevaluated for status of thyroid function. Operational definitions as large and moderate size goiters were described.47 patients, who had large or moderate size goiter for more than 20 years, fulfilled the inclusion criteriafor this study. These were evaluated for status of thyroid function.Results: 96% of patients with large or moderate size goiter of more than 20 years were hyperthyroid.Conclusion: A large goiter of more than 20 years duration should be investigated and managed with the suspicionof thyrotoxicosis